The last witch hunter [videorecording (DVD)] - Diesel, Vin; Wood, Elijah, 1981-; Caine, Michael; Owen, Rena, 1962-; Ólafur Darri Ólafsson (Lionsgate, 2016)
Tormented by the loss of his family and cursed with immortal life, the last witch hunter is all that stands between humanity and the combined forces of the most horrifying witches in history.